Philippine Business and the Regulatory Environment - Frias, Kristina Paola P. (Philippine Management Review; Vol 22 (2015), 2015)
This paper outlines and discusses the regulatory business environment in the Philippines with a focus on heavily regulated industries, the rationale for regulation, and the institutions performing regulatory functions. It examines several issues in regulation that Philippine business firms contend with to remain in operation, such as restrictions on ownership and price control; cost of compliance; ambiguity and varying interpretations of statutes by regulatory agencies; and conflict between national and local regulations. Likewise, it cites regulations that are not detrimental to the business community and are enacted to promote the development of an industry. The paper takes the position that regulation is not always detrimental to business development. Growth and development may ensue if the interests of the public and of the business community are taken into consideration and are balanced accordingly. It is imperative for regulators to remain neutral and to take into account the benefits and costs of regulation in order to design effective policies. The paper concludes by emphasizing the dynamic character of business regulations – posing both opportunities and threats to the business sector. It is, therefore, necessary that business firms are able to anticipate the impact of regulations, or if not, that they are flexible enough to respond or adjust to the change.